2014
DOI: 10.3109/0142159x.2014.886016
|View full text |Cite
|
Sign up to set email alerts
|

Undergraduate research: An innovative student-centered committee from the Kingdom of Saudi Arabia

Abstract: Research involvement by medical students is an essential need of the twenty-first century and models like URC could provide crucial platform for research training to the new generation of physician-scientists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
31
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 22 publications
1
31
0
Order By: Relevance
“…Moreover, graduating clinically-qualified and research-trained medical professionals emerges as a crucial healthcare necessity. In line with the above-mentioned notions, there is a rapidly mounting propensity towards incorporating structured scientific research training into undergraduate medical education 1 , 3 …”
Section: Introductionmentioning
confidence: 98%
“…Moreover, graduating clinically-qualified and research-trained medical professionals emerges as a crucial healthcare necessity. In line with the above-mentioned notions, there is a rapidly mounting propensity towards incorporating structured scientific research training into undergraduate medical education 1 , 3 …”
Section: Introductionmentioning
confidence: 98%
“…Over the next decade, numerous studies conducted in the USA, the UK, and Canada clearly demonstrated the benefits of involving undergraduates in research (Gillies & Marsh, 2013;Graham, Hempstead, & Couchman, 2012;Healey & Jenkins, 2009;Hensel, 2012;Kuh, 2008;Lopatto, 2010). Now recognized as a global phenomenon (Jenkins & Healey, 2010), the integration of research and teaching at the undergraduate level is taking hold in Australasia (Healey & Jenkins, 2009;Sandover, Partridge, Dunne, & Burkill, 2012), China (Wang & Wang, 2008;Yuhao, 2014), India (Padmaja, Laxmi Ramana, & Reddy, 2015), the Middle East (Alamodi et al, 2014;Ibnouf, Dou, & Knight, 2014), and the Netherlands (van der Rijst & Visser-Wijnveen, 2011), among other parts of the world. Both government and private funding drive the transformation of undergraduate education in countries such as Oman (Oman Research Council), Qatar (Qatar National Research Fund), and China (Yuhao, 2014).…”
mentioning
confidence: 99%
“…Recent scholars have discussed this problem in-depth, and modest but positive efforts have already begun to rectify this situation (6). However, we believe that it is the second of these two questions which forms the gist of the dilemma.…”
mentioning
confidence: 99%